MSG 328 – Introduction to Modelling - PPSM, Pusat Pengajian Sains Matematik (2022)
UNIVERSITI SAINS MALAYSIA Second Semester Examination 2021/2022 Academic Session July 2022 MSG 328 – Introduction to Modelling Duration : 2 hours